Theoretical Integration and Localized Practice: Implementing Creative Music Pedagogy within the National Curriculum Framework in Handan's Primary Schools - Song Jieyi; Suraya Amirrudin (International Journal of Education and Humanities, 2026)
This research examines the implementation of creative music pedagogy within China's national curriculum framework through a qualitative investigation of four primary schools in Handan, addressing tensions between standardized educational requirements and innovative pedagogical approaches. Using interpretive phenomenological analysis, the study involved 10 music educators and 3 administrators through semi-structured interviews, participant observation, and document analysis over 6 months. The investigation reveals that teacher adaptation follows a predictable five-phase developmental pathway, requiring 12 to 18 months for sustainable integration, progressing from initial resistance to strategic coordination. Cultural embedding involves complex negotiations as educators integrate local opera traditions and folk music elements within standardized frameworks, while sophisticated coordination strategies emerge, particularly "double professional life" approaches in which teachers maintain parallel professional identities to satisfy competing institutional demands while preserving creative authenticity. These findings demonstrate that meaningful educational innovation emerges through systematic teacher adaptation rather than policy reform alone, and that coordination mechanisms offer insights for other centralized education systems facing similar tensions between standardization and creativity. The investigation contributes to the theoretical understanding of educational change dynamics while providing evidence-based guidance for implementing sustainable creative pedagogy in highly regulated environments